Impacts of Food Delivery Culture on Dietary Health Among Young Adults in Shanghai - Tao Yang (Asia Pacific Economic and Management Review, 2025)
This study investigates the effect of delivery culture on diet health among young adults in Shanghai, motivated by increased reliance on delivery platforms and their associated health consequences. The study contrasts dietary intake, nutrition knowledge, and convenience-manipulated behavioral determinants. A mixed-methods study design involved a structured survey (n = 196) supported by semi-structured interviews (n = 15). Quantitative data were analyzed with descriptive statistics, correlation, and regression, and qualitative answers were coded thematically using NVivo. Sampling was conducted with stratified random and purposive sampling to obtain representativeness according to age, gender, and delivery use behavior. Correlation analysis results showed a small but statistically significant (r = 0.35, p < 0.001) correlation between the frequency of food delivery and perceived health deterioration. Regression analysis picked convenience as the strongest predictor for higher consumption, while nutrition awareness did not find a statistically significant protective factor. Descriptive statistics showed that while 61.23% believe they care about nutrition while ordering, 30.62% order healthy food frequently. Platform suggestions, price, and habit strongly predict poor interview options. The study summarizes that while consumers self-report being aware of nutritional issues, online influence and behavioral inertia thwart healthy intentions. It recommends mandatory nutritional labeling, AI-supported healthy recommendations, and reward-based platforms on delivery apps. The main limitations are self-reported measures, the threat of sampling bias, and the geographic location of Shanghai. Future studies should examine the impacts of longitudinal health and sample the population in other Chinese cities.